Causal Pathways Between Breast Cancer and Cardiovascular Disease Through Mediator Factors: A Two-Step Mendelian Randomization Analysis - Lu W; Li K; Wu H; Li J; Ding Y; Li X; Liu Z; Xu H; Zhu Y (Dove Medical Press, 2024)
Weilin Lu,1,* Kaiming Li,2,* Haisi Wu,2,* Jinyu Li,2 Yan Ding,2 Xiaolin Li,1 Zhipeng Liu,3 Huae Xu,2 Yinxing Zhu3,4 1The First Affiliated Hospital with Nanjing Medical University, Nanjing, People's Republic of China; 2Department of Pharmaceutics, School of Pharmacy, Nanjing Medical University, Nanjing, People's Republic of China; 3Taizhou Affiliated Hospital of Nanjing University of Chinese Medicine, Taizhou, People's Republic of China; 4Taizhou People's Hospital affiliated to Nanjing Medical University, Taizhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Huae Xu; Yinxing Zhu, Email xuhuae@njmu.edu.cn; zhuyinxing@njmu.edu.cnBackground: The causal relationship of breast cancer (BC) with cardiovascular disease (CVD) and the underlying mediating pathways remains elusive. Our study endeavors to investigate the causal association between BC and CVD, with a focus on identifying potential metabolic mediators and elucidating their mediation effects in this causality.Methods: In this study, we conducted two-sample Mendelian randomization (MR) to estimate the causal effect of BC (overall BC, ER+ BC, ER- BC) from the Breast Cancer Association Consortium (BCAC) on CVD including coronary heart disease (CHD), hypertensive heart disease (HHD), ischaemic heart disease (IHD), and heart failure (HF) from the FinnGen consortium. Then, we used two-step MR to evaluate 18 metabolic mediators of the association and calculate the mediated proportions.Results: Genetically predicted ER+ BC was causally associated with an increased risk of CVD including CHD (OR = 1.034, 95% CI: 1.004- 1.065, p = 0.026), HHD (OR = 1.061, 95% CI: 1.002- 1.124, p = 0.041), IHD (OR = 1.034, 95% CI: 1.007- 1.062, p=0.013), and HF (OR = 1.055, 95% CI: 1.013- 1.099, p = 0.010), while no causality was observed for overall BC and ER- BC. Furthermore, high-density lipoprotein cholesterol (HDL-C) was identified as a mediator of the association between ER+BC and CVD, including CHD (with 15.2% proportion)) and IHD (with 15.5% proportion), respectively.Conclusion: This study elucidates the potential causal impact of ER+ BC on subsequent risk of CVD, including CHD, HHD, IHD, and HF. We also outline the metabolic mediator HDL-C as a priority target for preventive measures to reduce excessive risk of CVD among patients diagnosed with ER+BC.Keywords: breast cancer, cardiovascular disease, ER status, Mendelian randomization, metabolic mediators, HDL-C